New Combinations and Growth - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
This paper develops an endogenous growth model based on the idea of new combinations of input factors as a growth mechanism. The model integrates the idea of several technologies used simultaneously in producing final output. Innovations are of the horizontal and vertical type and in addition of the type of new technologies which can be combined with existing ones. All types of innovations are endogenous and the occurrence of a new technology has stochastic elements as well. This leads to endogenous dynamics in the growth rates of final output production.
urn:nbn:de:bvb:384-opus4-711466
Keywords: O31; O41; 330; Endogenous growth; new combinations